Things no longer there : a memoir of losing sight and finding vision - Krieger, Susan (Book collections on Project MUSE., 2005)
A collection of personal stories about the author's struggle toward enlightenment while losing her eyesight. It is also, more broadly, about invisible landscapes--places of the heart that linger long after they have disappeared from the world outside.--From publisher description.